Gold-catalyzed reaction of oxabicyclic alkenes with electron-deficient terminal alkynes to produce acrylate derivatives - Sun, Yin-wei; Xu, Qin; Shi, Min (Beilstein Journal of Organic Chemistry, 2013)
Oxabicyclic alkenes can react with electron-deficient terminal alkynes in the presence of a gold catalyst under mild conditions, affording the corresponding addition products in moderate yields. When using alkynyl esters as substrates, the (Z)-acrylate derivatives are obtained. Using but-3-yn-2-one (ethynyl ketone) as a substrate, the corresponding addition product is obtained with (E)-configuration. The proposed mechanism of these reactions is also discussed.
Keywords: gold catalysis; oxabicyclic alkenes; substituted acrylates